2010
DOI: 10.1186/1475-925x-9-63
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the soft tissue biocompatibility of MgCa0.8 and surgical steel 316L in vivo: a comparative study in rabbits

Abstract: BackgroundRecent studies have shown the potential suitability of magnesium alloys as biodegradable implants. The aim of the present study was to compare the soft tissue biocompatibility of MgCa0.8 and commonly used surgical steel in vivo.MethodsA biodegradable magnesium calcium alloy (MgCa0.8) and surgical steel (S316L), as a control, were investigated. Screws of identical geometrical conformation were implanted into the tibiae of 40 rabbits for a postoperative follow up of two, four, six and eight weeks. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 45 publications
5
97
3
Order By: Relevance
“…Magnesium ions are a natural component of the body [7] . Furthermore, magnesium alloys were tested as non-allergic [8] and have a lower immunogenic potential than surgical steel or titanium [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium ions are a natural component of the body [7] . Furthermore, magnesium alloys were tested as non-allergic [8] and have a lower immunogenic potential than surgical steel or titanium [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Both alloys were chosen because of their promising biomechanical properties, and both had been evaluated in vivo in previous studies. [13][14][15][16][17][18][19][20][21] ZEK100 pins have shown promising initial mechanical stability. 15,20 Lensing et al reported good biocompatibility and an osteoconductive effect of ZEK100 in the middle ear of rabbit.…”
Section: Introductionmentioning
confidence: 99%
“…1,25 Several studies have investigated the properties and corrosion behavior of binary magnesium-calcium alloys. 13,14,18,19,[26][27][28][29][30] The addition of calcium provides solid solution strengthening and contributes to grain refinement owing to grain boundary strengthening. 1 It was observed that the addition of calcium above the solubility limit of approximately 1.34 wt% Ca enhanced the corrosion rate.…”
Section: Introductionmentioning
confidence: 99%
“…This type of soft tissue reaction is also present in the exposed parts of orthopaedic implants. Erdmann et al [131] compared orthopaedic screws made from Mg-0.8Ca and 316L stainless steel implanted into the tibiae of New Zealand white rabbits. Both implants were tolerated well, and had similar inflammatory reactions.…”
Section: Consideration For Selecting An Appropriate In Vivo Modelmentioning
confidence: 99%